Characterization of Irrigated and Rainfed Saline Vertisols of Bara Tract (Bharuch) of Gujarat - Kumar, Shrvan; Das, Amaresh; Chinchmalatpure, Anil R.; Prasad, Indivar (Annals of Arid Zone, 2023)
Four representative pedons (2-irrigated and 2-rainfed areas) were studied,interpreted and horizon-wise sampled as per standard procedure (Soil Survey Staff,1995) to characterize the salt affected soils of Bara tract of district Bharuch, Gujarat.Soil samples were collected at horizon-wise differentiation to a depth up to 150 cm.In general, soil color was dark brown (10YR 4/3) or very dark grayish brown (10YR3/2) or very dark brown (10YR 2/2) with clayey texture having structure varying frommedium moderate sub-angular to coarse strong angular blocky. Pedons were classifiedup to a family level where temperature regime is Hyperthermic and texture is fine withMontmorillonite. Classification up to sub group level were as follows: pedon 1- EnticChromusterts, pedon 2-(calcareous) Entic Chromusterts, pedon 3 and 4 (calcareous),Udorthentic Chromusterts. Soil pH, ECe, SOC, CaCO3, CEC and ESP of irrigated pedonsvaried respectively from 7.78 to 8.57, 0.75 to 12.50 dS m-1, 2.2 to 7.2 g kg-1, 2.6 to 196.4 gkg-1, 39.0 to 52.3 cmol (p+) kg-1 and 3.3 to 27.1, while the corresponding values in rainfedpedons were 8.29 to 8.85, 0.75 to 8.90 dS m-1, 2.6 to 5.7 g kg-1, 2.6 to 272.1 g kg-1, 36.9 to50.7 cmol (p+) kg-1 and 2.8 to 18.1, respectively. Salinity/or Sodicity and calcareousnesswas occurred at sub-surface layers in irrigated saline Vertisols. Soil saturation extractrevealed the dominance of Na+ cation followed by Mg2+, Ca2+ and K+, while in anionsthe trend was Cl->SO42-~HCO3-+CO32-. SAR values were higher in irrigated conditionsas compared to rainfed. The higher ESP was found due to regular irrigation of canal/borewell/tubewell water etc. which ultimately induced the sodification process in thesurface as well as sub-soils, while higher ESP was found in lower soil depths andtends to be sodic. The study thus advocates that continuing the present anthropogenicactivities might render the soils unsuitable for agricultural production in the future.Further, looking at the sodicity/salinity build up, physical nature of Vertisols as wellas groundwater quality constraints, suggests that it would be prudent to encourageirrigated/ or rainfed agriculture in the areas under improved management practices tosustainable crop production and improve the soil health.